2002
DOI: 10.4049/jimmunol.169.6.3015
|View full text |Cite
|
Sign up to set email alerts
|

Major Differences in Antigen-Processing Correlate with a Single Arg71↔Lys Substitution in HLA-DR Molecules Predisposing to Rheumatoid Arthritis and with Their Selective Interactions with 70-kDa Heat Shock Protein Chaperones

Abstract: Several HLA-DR alleles are genetically associated with rheumatoid arthritis. DRB1*0401 predominates in Northern Europe and has a characteristic 70QKRAA motif. This sequence contacts bound peptides and the TCR. Further interactions have been suggested with additional proteins during Ag loading. We explored the much stronger processing/presentation of full-length recombinant human acetylcholine receptor α subunit to a specific T cell clone by APC from DRB1*0401+ than *0408+ donors. Using DR*04 transfectants, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
0
25
0
3
Order By: Relevance
“…It has been shown for both MHC class I-and II-dependent systems that hsp70 complexes with proteins are more immunogenic than proteins alone [20][21][22][23][24][25][26][27][28][29]. This has been related to enhancement of antigen presentation by hsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown for both MHC class I-and II-dependent systems that hsp70 complexes with proteins are more immunogenic than proteins alone [20][21][22][23][24][25][26][27][28][29]. This has been related to enhancement of antigen presentation by hsp.…”
Section: Discussionmentioning
confidence: 99%
“…While most data on the contribution of hsp-peptide interactions have addressed immune responses involving MHC class Idependent pathways [21][22][23][24], more recent results from this [25], and other [26][27][28][29] laboratories indicate that hsp are also capable of participating in antigen presentation in MHC class II-dependent pathways. In this respect, hsp70 is a major hsp implicated in the formation of immunogenic complexes and the facilitation of MHC presentation.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that overexpression of the constitutively expressed Hsc73 in a macrophage cell line led to an increased presentation of exogenous antigen via MHC class II [13]. Moreover, E. coli HSP70 DnaK was found to enhance the processing and presentation of exogenous antigen to a human CD4 + T cell clone, whereas the effect was dependent on the allelic variants of HLA-DR [14]. A direct interaction between HLA-DR-derived peptide fragments and HSP70 molecules was demonstrated by our group, showing that only peptide fragments derived from HLA-DR molecules associated with protection from rheumatoid arthritis (RA) did not bind to HSP70 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Dieselbe T-Zelle kann ein "high responder" oder ein "low responder" sein! Wir konnten mit Transfektanten zeigen, dass der Unterschied nur vom Austausch Lys 71 ↔ Arg 71 (*0401 ↔ *0408) herrührt, der die Bindung des Epitops nicht beeinträchtigt, und dass die rekombinante a-Untereinheit des AChR das E. coli DnaK enthielt [20]. Dieses ist für effizientes Prozessieren des Antigens und Präsentieren des Epitops durch *0401 + APZ absolut notwendig [20].…”
Section: Melchers Immungenetikunclassified
“…Wir konnten mit Transfektanten zeigen, dass der Unterschied nur vom Austausch Lys 71 ↔ Arg 71 (*0401 ↔ *0408) herrührt, der die Bindung des Epitops nicht beeinträchtigt, und dass die rekombinante a-Untereinheit des AChR das E. coli DnaK enthielt [20]. Dieses ist für effizientes Prozessieren des Antigens und Präsentieren des Epitops durch *0401 + APZ absolut notwendig [20]. Wir nehmen daher an, dass sich das Antigen in einem Komplex mit DnaK befand, aus dem heraus es in die Tasche des *0401-Moleküls geladen werden konnte, nicht aber in die des *0408-Moleküls (Abb.…”
Section: Melchers Immungenetikunclassified